Athens, the allies and the empire: symbolai and symbola between the fifth and fourth centuries BCE (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
The aim of this article is to focus on chs. 2 and 4 of Philippe Gauthier’s Symbola and assess to what extent his main argument - underlining the difference between fifth-century «commercial» (and procedural) symbolai and fourth-century «judicial» (and substantive) symbola - is still valid. The starting point is that symbolai were themselves part of a wider picture including political charges arising in allied poleis tried by the Athenian courts and «administrative» cases also adjudicated in Athens. In the first part of the article, it is argued that the boundaries between symbolai and symbola were more blurred that Gauthier assumed. Trials apo sumbolōn, when attested in fifth century Athenian decrees, clearly do not only concern commercial cases. The term symbolaion, in particular, has a broader (and more technical) meaning than «affaire», «rapport d’affaire» (Gauthier) or «contract», and can be shown to refer to obligations both ex delicto and ex contractu. Symbolai, in other words, covered legal cases concerning persons and property. The second part of the article focuses on some important perspectives suggested by Gauthier’s book with regard to the Athenian empire and Athens’ relations with her allies. It is maintained that the Delian league was also an economic system which entailed, right from its establishment, the creation of a network of interstate agreements that made free and safe circulation of persons and goods possible.
Keywords: Ancient Greek law; Athens; interstate agreements; trade; Delian league